INTELLIGENT AUTOMATION WITH IBM CLOUD PAK FOR BUSINESS AUTOMATION a practical guide to automating enterprise business workflows to deliver intelligent solutions - Chan, Allen; Trinh, Kevin; Molines, Guilhem; Samoojh, Suzette; Kinder, Stephen (PACKT PUBLISHING LIMITED, 2022)
Leverage the low-code/no-code approach in IBM Cloud Pak for business automation to accelerate your organization's digital transformation Purchase of the print or Kindle book includes a free eBook PDF Key Features Get a comprehensive understanding of IBM Cloud Pak for Business Automation Take a deep dive into insights on RPA, workflow automation, and automated decisions Deploy and manage production-grade automated solutions for scalability, stability, and performance Book Description COVID-19 has made many businesses change how they work, change how they engage their customers, and even change their products. Several of these businesses have also recognized the need to make these changes within days as opposed to months or weeks. This has resulted in an unprecedented pace of digital transformation; and success, in many cases, depends on how quickly an organization can react to real-time decisions. This book begins by introducing you to IBM Cloud Pak for Business Automation, providing a hands-on approach to project implementation. As you progress through the chapters, you'll learn to take on business problems and identify the relevant technology and starting point. Next, you'll find out how to engage both the business and IT community to better understand business problems, as well as explore practical ways to start implementing your first automation project. In addition, the book will show you how to create task automation, interactive chatbots, workflow automation, and document processing. Finally, you'll discover deployment best practices that'll help you support highly available and resilient solutions. By the end of this book, you'll have a firm grasp on the types of business problems that can be solved with IBM Cloud Pak for Business Automation. What you will learn Understand key IBM automation technologies and learn how to apply them Cover the end-to-end journey of creating an automation solution from concept to deployment Understand the features and capabilities of workflow, decisions, RPA, business applications, and document processing with AI Analyze your business processes and discover automation opportunities with process mining Set up content management solutions that meet business, regulatory, and compliance needs Understand deployment environments supported by IBM Cloud Pak for Business Automation Who this book is for This book is for robotic process automation (RPA) professionals and automation consultants who want to accelerate the digital transformation of their businesses using IBM automation. This book is also useful for solutions architects or enterprise architects looking for best practices to build resilient and scalable AI-driven automation solutions. A basic understanding of business processes, low-code visual modeling techniques, RPA, and AI concepts is assumed.